First high resolution ro-vibrational study of the (0200), (0101) and (0002) vibrational states of MGeH4 (M=76,74); Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 182 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Raspopova N. I. Natalya Ivanovna; Fomchenko A. L. Anna Leonidovna; Sennikov P. G. Petr Gennadievich; Koshelev M. A. Maxim Alexandrovich; Velmuzhova I. A.; Velmuzhov A. P. Alexander Pavlovich (2016, 2016)
Title screen